Charge transfer mechanism of WO3/TiO2 heterostructure for photoelectrochemical water splitting - Castro, I. A.; Byzynski, G. [UNESP]; Dawson, M.; Ribeiro, C. (Elsevier, 2017)
The present study shows how electronic parameters (e.g. band gap energy, band edge positions) on semiconductors affect photoelectrochemical activity in simulated solar light using WO3, TiO2 and WO3/TiO2 as model systems. Hydrothermal synthesis was conducted to study heterostructure (HE) formation, which the loading of WO3 in TiO2 structure were varied to 20, 40 and 80 wt%. Scanning electron microscopy images show that WO3 and TiO2 particles are in contact with each other and the synthesis method as well as the deposition method are appropriate for the formation of WO3/TiO2 HE film. Important findings were obtained with a hole scavenger during photoelectrochemical characterization of WO3/TiO2–40 wt% film. This strategy was effective to clearly distinguish charge transport from charge separation, the essential mechanisms that affect water splitting which are often misinterpreted experimentally for HE. The hole scavenger experiment depicts the increase by 17.5% in photocurrent density for the WO3/TiO2–40 wt% film as compared to WO3 film, corresponding to 210 and 12 μA cm−2 vs Ag/AgCl respectively. Additionally, this HE film showed water oxidation initiated at lower applied potentials and indicating that coupling of the materials resulted in optimization of band edge properties for water splitting with the increase on light absorption at the visible range. Flat band potential was determined by the Mott-Schottky plot and it indicated the difference of 1.08 V vs Ag/AgCl between TiO2 and WO3 potentials, which makes the charge injection from one structure to another effective and thermodynamically stable for charge separation. A charge carrier density of 1.59 × 1020 was observed for the WO3/TiO2–40 wt% and it supports the best photoelectrochemical performance for water oxidation.
Keywords: Band edge manipulation; Charge recombination; Electron-hole pairs; Heterostructure; Hole scavenger; Titanium oxide; Tungsten oxide